Implementasi Sistem Pemerintahan Good Governance menurut Ibnu Taimiyah dalam Pembangunan Masyarakat Indonesia - Muhammad Azrul Amirullah; An-Nafsi Ma’rifatul Huda (Lembaga Yasin AlSys, 2025)
The integration of Islamic values into local governance practices is a critical priority in the context of community development at the village level, given the strategic role of village governments in public service delivery, budget management, and the empowerment of citizen participation. This study aims to examine the implementation of good governance principles, based on the thought of Ibn Taymiyyah, within village governance practices in East Java. A qualitative approach was employed, using literature review and in-depth interviews with village heads across several regions. The findings reveal that Ibn Taymiyyah’s concept of good governance emphasizes public welfare through the development of strategic sectors such as politics, society, education, and the economy. At the core of sound governance is social justice, which, according to Ibn Taymiyyah, must be realized by the state or governing authorities, regardless of the form or name of the institution. Field implementation shows that many villages have begun to adopt these principles through mechanisms such as village deliberations (musyawarah desa), budget transparency, and the establishment of internal oversight bodies. However, challenges remain in strengthening integrity, leadership ethics, and the consistent application of Islamic values. The study concludes by underscoring the importance of enhancing the moral and spiritual capacity of local leaders and the need for systematic integration of Islamic values into village governance. The implications include contributions to the literature on the Islamization of public governance and policy recommendations for ethically grounded village development.